Effect of long chain fatty acids on biogas production and biochemical kinetics in anaerobic bioreactors: a review - Kahar, Abdul; Khoiroh, Ianatul (Universitas Lambung Mangkurat, 2024)
Long Chain Fatty Acids (LCFAs) are the primary intermediate byproduct of the lipid (fats, oils, and greases) degradation process, and if they accumulate in high concentrations, they can cause failure or reduce the performance of anaerobic bioreactors due to sludge flotation issues, biochemical kinetics problems for soluble substrates, inhibition of microbial activity, and inefficient biogas recovery. Understanding the biochemical kinetics of anaerobic bioreactors requires taking into account the entire process, including microbe growth, substrate degradation, and product synthesis. Biochemical kinetics of anaerobic treatment is the study of polymer biodegradation rates of insoluble organic matter in wastewater, which is the mechanism of bond breaking and bond formation in biochemical reactions. As a result, biochemical kinetics allow for the design of both desired and undesirable reaction phases. The kinetic parameters acquired are utilized to design, operate, and optimize anaerobic bioreactors for wastewater treatment on a technical scale.